Implementasi Metode Dengar Ucap Pada Pembelajaran Bahasa Arab Di Pondok Pesantren Ar-Raudhatul Hasanah - Saragih, Fuji Anugrah; Mavianti, Mavianti (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This article will discuss how the audiolingual method is used to teach maharah kalam. In maharah kalam learning, only a few students can express their thoughts orally, to overcome this problem the teacher can apply the audiolingual method. This research method uses qualitative research. The data collection techniques used in this research are observation, interviews and documentation. The aim of this research is to find out how female students at the Ar-raudhatul Hasanah Islamic boarding school use a hearing-speech approach in learning Arabic. Based on the research results, it was concluded that the listening-to-speech method or audiolingual method is an effective method used at the Ar-Raudhatul Hasanah Islamic Boarding School, although there are still some students who have difficulty memorizing Arabic vocabulary due to internal problems. The audio-lingual method in Islamic boarding schools emphasizes language mastery through direct listening and speaking, so it is effective for improving speaking and listening skills quickly. It is easier for female students to internalize pronunciation, intonation and vocabulary, and relate language use to everyday situations, strengthening their understanding.